Study on the influence factors of the release characteristics of IQOS cigarette smoke. Issue 5 (May 2020) - Tong, Yuxing; Xiong, Zhe; Gao, Song; Yan, Qunshan; Liu, Zhichang; Wang, Ziwei; Le, Xi; Shu, Hao; Tang, Xiangbin; Li, Pengfei; Xiong, Yimin; Wang, Yi
Abstract: In order to clarify the reasons for the good smoke release characteristics of IQOS, the factors that are beneficial to the smoke release characteristics of IQOS were studied by comparing the K (the amount of released smoke was less) and IQOS. The components of IQOS and K which were easy to be released were characterized by the GC-MS. The thermal release characteristics of IQOS, K and the original tobacco powders of K were characterized by the thermogravimetric analyzer (TG). The main compounds of the released smoke of IQOS and K were characterized by Py/GC-MS at two typical heating temperatures (260 and 330°C). The results show that: 1) the actual heating temperature of the IQOS was higher (330°C), which could promote the release of smoke. 2) IQOS tobacco stick has a porous structure with higher specific surface area, which was beneficial to the release of smoke. 3) IQOS contains more components which were easy to be released, thus the high concentration of smoke could be formed. 4) Though the content of the atomization agent in IQOS was lower than that in K, more atomization agent in IQOS could be released at the tobacco cracking temperature (330°C), thus the atomization property of IQOS was better.